Mixed convection flow of Powell-Eyring fluid over a stretching cylinder with Newtonian heating - Hafiz A. Wahab; Sajjad Hussain; Muhammad Naeem (Kuwait Journal of Science)
The aim of this article is to analyze the mixed convection flow of Powell-Eyring fluid induced by inclined stretchingcylinder. Heat transfer analysis is subjected to the Newtonian heating and heat generation/absorption. A system of nonlinearpartial differential equations is converted to a system of ordinary differential equations by suitable transformations. Theseries solution of the present problem is solved by homotopy analysis method. Behaviors of various parameters onskin friction coefficient, Nusselt number, velocity and temperature profiles are discussed. A comparison of skin frictioncoefficient for viscous and Powell-Eyring fluids with the previous existing data is also presented.